(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Competition is one of the most important challenges that is facing the marketing of industrial products in today’s markets. In this research study of the impact of material selection factor for air coolers of different materials is applied. Investigation on the air cooler windows which are part of the body of air coolers is conducted. Corrosion resistance, thermal conductivity, strength of material, weight, shape, cost and manufacturing process are the factors that are applied and calculated on three types of materials Aluminum, Galvanized steel and polypropylene. The physical properties of the three mentioned materials are used to calculate Merit Index .The corrosion average, according to Tafel Method depending the corrosion current and adopting contactors for the anodic and cathodic metals behaviors is performed. ANSYS is adopted using the three samples for the selected materials Aluminum, Galvanized steel and polypropylene to measure maximum stress and deflection are measured. Accordingly, the results are compared to choose the best alternative. It is observed that the polypropylene is the best choice depending three factors while the aluminum material is better depending two factors and the galvanized steel is regarded as the best in only one factor, the rest factors are identical when choosing an alternative material for manufacturing the air cooler windows.